2000
DOI: 10.1089/152581600319405
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effects of TNF-alpha, TGF-beta1, and Chemokines on Megakaryocytic Colony Formation in CD34+Cells Derived from Umbilical Cord Blood Compared with Mobilized Peripheral Blood and Bone Marrow

Abstract: CD34+ cells from human umbilical cord blood (CB) were isolated and investigated for megakaryocytic (MK) colony formation in response to recombinant human (rh) stimulatory and suppressive cytokines and compared with their counterparts in normal BM and G-CSF-mobilized peripheral blood (mPBL). First, we observed that IL-11 by itself at any dosage had no stimulator activity on MK colony formation derived from CD34+ cells in CB, mPBL, and BM. IL-3, steel factor (SLF), or thrombopoietin (Tpo) alone stimulated number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In human promyelocytic leukemia cells (HL-60), both inhibit cell growth, which is associated with down-regulation of c-myc expression (40). In hematopoietic stem cells, hematopoietic progenitor cells and cord blood megakaryocytes (MK), TNF-a and TGF-b can inhibit cell proliferation and colony-forming ability (41,42). It has also been found that in mouse hepatocytes, TGF-b1 can inhibit the production of hepatic growth factor (HGF), while TNF-a is positively correlated with the production of TGF-b, and inhibiting the level of TNF-a can inhibit the production of TGF-b1, thereby enhancing liver tissue regeneration (43).…”
Section: Role Of Tnf-a and Tgf-b In Cell Proliferationmentioning
confidence: 99%
“…In human promyelocytic leukemia cells (HL-60), both inhibit cell growth, which is associated with down-regulation of c-myc expression (40). In hematopoietic stem cells, hematopoietic progenitor cells and cord blood megakaryocytes (MK), TNF-a and TGF-b can inhibit cell proliferation and colony-forming ability (41,42). It has also been found that in mouse hepatocytes, TGF-b1 can inhibit the production of hepatic growth factor (HGF), while TNF-a is positively correlated with the production of TGF-b, and inhibiting the level of TNF-a can inhibit the production of TGF-b1, thereby enhancing liver tissue regeneration (43).…”
Section: Role Of Tnf-a and Tgf-b In Cell Proliferationmentioning
confidence: 99%
“…It is well established that T cell responses are crucial for clearing viral-infected cells and controlling viral replication. T cell responses are beneficial to host immune defense against HIV infection [ 32 , 33 ], and CD4 + T cell responses are critical for humoral responses. We evaluated the T cell responses (Ag-specific Th1- and Th2 associated cytokine induction) induced by various VLPs.…”
Section: Discussionmentioning
confidence: 99%